Real-Time Diminished Reality Application Specifying Target Based on 3D Region - Kaito Kobayashi; Masanobu Takahashi (Virtual Worlds, 2024)
Diminished reality (DR) is a technology in which a background image is overwritten on a real object to make it appear as if the object has been removed from real space. This paper presents a real-time DR application that employs deep learning. A DR application can remove objects inside a 3D region defined by a user in images captured using a smartphone. By specifying the 3D region containing the target object to be removed, DR can be realized for targets with various shapes and sizes, and the specified target can be removed even if the viewpoint changes. To achieve fast and accurate DR, a suitable network was employed based on the experimental results. Additionally, the loss function during the training process was improved to enhance completion accuracy. Then, the operation of the DR application at 10 fps was verified using a smartphone and a laptop computer.